Assessment of health management information system for monitoring of maternal health in Jaleswar Block of Balasore District, Odisha, India - Ranjit Kumar Dehury; Suhita Chopra Chatterjee (Wolters Kluwer Medknow Publications, 2018)
Background: In 2005, the Government of India implemented the National Rural Health Mission for reduction of maternal mortality. One of the major impediments in improving maternal health since then has been a poor management of the Health Management Information System (HMIS) at grass-roots level which could integrate data collection, processing, reporting, and use of information for necessary improvement of health services. Objective: The paper identifies the challenges in generating information for HMIS and its utilization for improvement of maternal health program in the tribal-dominated Jaleswar block in Odisha, India. It also aims to understand the nature and orientation of the HMIS data generated by the government for the year 2013-2014. Methods: The study is a cross-sectional type which used observation and interview methods. Primary data were gathered from health professionals to understand the challenges in generating information for HMIS and its utilization. Next, to understand the nature and orientation of HMIS, data pertaining to tribal block were analyzed. Results: The findings show that there are challenges in generation of quality data, capacity building of workforce, and monitoring of vulnerable tribal population. The discrepancies between HMIS data and field reality display the gap in formulation of policy and its implementation. Conclusion: The study unearths the existing politics of knowledge generation. This shows highly standardized procedures and information gathering by use of dominant biomedical concepts of maternal health with limited inclusion of local birthing conceptions and needs of vulnerable tribal pregnant women.